Foam Mat Drying of Papaya - Meena, Anju; Jawake, Pravin; Jain, S. K.; Mudgal, V. D.; Saloda, M. A.; Sharma, K. C. (Journal of Agricultural Engineering, 2015)
A study was carried out to produce papaya powder using egg albumin as foaming agent and methyl cellulose as foam stabilizer under foam-mat drying technique. A foam producing unit consisting of air compressor, mixer, pressure gauge and PVC pipe line as connecting device was developed. Foams were prepared from papaya pulp by adding egg albumin (0.2%) and methyl cellulose (0.5%) at air velocity of 1.3, 1.5 and 1.7 m.s-1, whipping for 5, 10 and 15 min and 720, 930 and 1440 rpm speed of mixer. The maximum foam expansion, foam stability and foam density were 20.67%, 29.32% and 0.965 g.cm-3, respectively. The foams were dried in a tray dryer at air temperature of 60°C and constant air velocity of 1.5m.s-1with foam thickness of 10 mm. Moisture diffusivity varied in the range of 2.03 ×10-8 m².s-1 and 2.23×10-8 m².s-1 during drying of papaya pulp. The maximum and minimum value of wate activity was obtained 0.291 and 0.207. The maximum value of chroma was 37.55. The sensory values for papaya powder were more than 7.5 for colour, taste, appearance and overall acceptability.